Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Could anyone help me to do this integral ?

$$\int_{\,0}^\infty \; \frac{\exp \left( -\frac{1}{x} -x\right)}{\sqrt{x}} \, dx = \sqrt{\pi}e^{-2} $$

I think you start with completing the square in the exponent, but what substitution do you make then ? $u=\sqrt{x}$ didn't seem to get me far.

share|improve this question
    
Are you familiar with Error Functions? –  Inquest Oct 15 '12 at 18:17
    
Does $\displaystyle \frac{1}{\sqrt x}= \frac{2}{\sqrt{\pi}} \int_{0}^{\infty} e^{-xt^2} dt$ help? Anyway, (+1) for the question. –  Chris's sis Oct 15 '12 at 18:18
1  
@JoeKing: This is a special case of the integral dealt with here. This is the case $n = t = 1/\sqrt{\pi}$. –  user26872 Oct 15 '12 at 20:17
add comment

1 Answer

up vote 10 down vote accepted

Substitute first $x=u^2$ in order to have:

$$ I = \int_{0}^{+\infty}\frac{dx}{\sqrt{x}\exp\left(x+\frac{1}{x}\right)}=2\int_{0}^{+\infty}e^{-\left(x^2+\frac{1}{x^2}\right)}\,dx$$

Use now the substitution $x=\frac{1}{y}$ to have:

$$ I = 2\int_{0}^{+\infty}\frac{1}{x^2}e^{-\left(x^2+\frac{1}{x^2}\right)}\,dx,$$

from which follows:

$$ I = \int_{0}^{+\infty}\left(1+\frac{1}{x^2}\right)e^{-\left(x^2+\frac{1}{x^2}\right)}\,dx,$$

and the key substitution is now $u = x-\frac{1}{x}$, from which we have:

$$ I = \int_{-\infty}^{+\infty}e^{-u^2-2}\,du = e^{-2}\sqrt{\pi}, $$

QED.

share|improve this answer
    
Nice and simple (+1). –  Chris's sis Oct 15 '12 at 18:30
    
Wow. I would never have worked that out. Was it obvious to you ? –  Joe King Oct 15 '12 at 18:45
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.